First observation of the decay λ0b→ηc(1S)pK- - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2020)
The decay Λ0b→ηc(1S)pK− is observed for the first time using a data sample of proton-proton collisions, corresponding to an integrated luminosity of 5.5 fb−1, collected with the LHCb experiment at a center-of-mass energy of 13 TeV. The branching fraction of the decay is measured, using the Λ0b→J/ψpK− decay as a normalization mode, to be B(Λ0b→ηc(1S)pK−)=(1.06±0.16±0.06+0.22−0.19)×10−4, where the quoted uncertainties are statistical, systematic and due to external inputs, respectively. A study of the ηc(1S)p mass spectrum is performed to search for the Pc(4312)+ pentaquark state. No evidence is observed and an upper limit of B(Λ0b→Pc(4312)+K−)×B(Pc(4312)+→ηc(1S)p)B(Λ0b→ηc(1S)pK−)<0.24 is obtained at the 95% confidence level.
Im Titel werden "lambda" und "eta" als griechische Buchstaben dargestellt
Im Titel ist der Buchstabe "c" tiefgestellt, das Minuszeichen hochgestellt
Im Titel ist die Zahl "0" hochgestellt, der Buchstabe "b" tiefgestellt
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, G. Frau, D. Gerick, J. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, H. Malygina, J. Marks, D.A. Unverzagt, U. Uwer, L. Witola, A. Zhelezov [und viele weitere]
Gesehen am 04.02.2022